Production of Spray-Dried Coconut Milk Powder - Hassan, Mohd Ali (1987)
The production of coconut milk powder could be carried out, even though the fat content of fresh coconut milk is above 30%. The spray drying process was used with an air inlet and outlet temperatures of 190°C and 90°C respectively. Additives were found to be necessary and suitable ones identified in this study are skim milk and dextrin in the range of10% -15% w/w and 5% - 7% w/w respectively. The product obtained resembles cow milk and can easily be reconstituted with water either at 30°C or 100°C giving a homogeneous solution. The spray dried powder is stable during storage in polyethylene package under room conditions even after three months, giving a satisfactory reconstituted product.